Inhalatory therapy training: a priority challenge for the physician - Melani, A.S. (Acta Biomedica Atenei Parmensis, 2007)
Patients with asthma and COPD commonly use inhaled drugs. The 3 types of currently available devices for inhaled therapy (Metered-dose inhaler, dry powder inhaler, and nebulizer) are clinically equivalent. However, since many different inhalers are available for inhaled therapy, the choice of the delivery device is important for optimizing the results of aerosol therapy.Traditional press-and-breathe Metered Dose Inhalers (pMDIs) have recently improved their ecological appeal, can be used in every clinical and environmental situation, their dosing is convenient and highly reproducible, but their efficient delivery remains highly technique dependent. Poor inhalation technique can be minimised by the use of add-on valved holding chambers, which are seldom used in the clinical practice possibly because they are cumbersome. Breath Actuated devices (BAIs), such as Dry Powder Inhalers (DPIs), which are environmental-friendly, safe, effective, reliable, portable and self-contained, overcome problems of handbreath co-ordination associated with pMDIs usage, but their use is also undermined by common errors of inhalation technique in real life. Nebulizers are cumbersome and time-comsuming for use and maintenance, but their use needs less cooperation than inhalers. Although nebulizer practice is not always evidence-based, some patients, mainly elderly prefer nebulizers for regular long-term usage. Despite the introduction of newer devices, clear advantages of a particular delivery system over other inhalers in terms of compliance, preference, and cost-effectiveness are not currently available. The objective of an ideal and easy-to use inhaler is far from reality. Patient education is the critical factor in the use and misuse of delivery devices and effectiveness of aerosol therapy. The choice of the device has to be tailored according to the patient’s needs, situation, and preference. Whatever the chosen inhaler, education from health caregivers has a key-role for improving inhaler technique and compliance. Differences among delivery devices represent another challenge to patient use and caregiver instruction.